Sabedoria popular dos pescadores do norte do Espírito Santo: contexto conservacionista de Epinephelus itajara (Lichtenstein, 1822). - Herculano, Henrique Campiao (2019)
The Goliath Grouper (Epinephelus itajara) features reduced populations in your entire ocurrence area, because of the overfishing, and the loss of the breeding habitats and the growth sites like mangroves. In addition to having slow growth rates, performs reproductive aggregation, sexually late maturity and are territorialist. Because of this factors and the verified reduction of the species, the goliath grouper is in the red list of the threatened with extinction species of UICN. E. itajara can reach weights above 400kg and live more than 38 years. Use to be founded next to shipwrecks, bridge pillars, stone sites and rocky shore tips. With the use of the Local Ecological Knowledge (LEK), this methodology find in its principles and reliability on the intrinsic knowledge of the more experienced and recognized fishermen by the local community, thus it has been established as an important tool about the most various environmental actors. Twenty-six key fishermen from the ES north region were interviewed through LEK, at first was identified a community with low income and educational level. However, the flavours about the aspects of the species biology was vast, presented, clearly, important items of the diet, like crab and catfish, seasonality of species, the first maturation phase and habitat description of the juveniles and adults at the region. These data were compatible with the works published with the same thematic and ecology and reproduction areas of E. itajara. Through LEK, was identified a local population decline of 68% along 4 decades, was unanimous the need for conservation of the grouper among the interviewees and was possible identify 22 ocurrence points with 3 probably places of reproductive aggregation at the region. These data show us the need for maintenance of the protection of the species secretary, reclassification and expansion of the Conservation Units of the region and, mainly, a greater involvement of the local community in decision-making in relation to existing UCs, obeying the Decree n° 6040, of February 7th, 2007, that guarantees the participation of the populations involved in the elaboration of public policies regarding their area of use.